Helium-induced swelling and mechanical property degradation in ultrafine-grained W and W-Cu nanocomposites for fusion applications. (May 2022) - Wurmshuber, Michael; Balooch, Mehdi; Huang, Xi; Hosemann, Peter; Kiener, Daniel
Abstract: Besides high dose radiation and extreme thermal loads, a major concern for materials deployed in novel nuclear fusion reactors is the formation and growth of helium bubbles. This work investigates the swelling and mechanical property degradation after helium implantation of ultrafine-grained W and nanocrystalline W-Cu, possible candidates for divertor and heat-sink materials in fusion reactors, respectively. It is found that ultrafine-grained W and single crystalline W experience similar volumetric swelling after helium implantation but show different blistering behavior. The W-Cu nanocomposite, however, shows a reduced swelling compared to a coarse-grained composite due to the effective annihilation of radiation-induced vacancies through interfaces. Furthermore, the helium-filled cavity structures lead to considerable softening of the composite. Graphical abstract: Image, graphical abstract